Interplay of higher plants with lithium pollution: Global trends, meta-analysis, and perspectives. (January 2023) - Shakoor, Noman; Adeel, Muhammad; Azeem, Imran; Ahmad, Muhammad Arslan; Zain, Muhammad; Abbas, Aown; Hussain, Muzammil; Jiang, Yaqi; Zhou, Pingfan; Li, Yuanbo; Xu, Ming; Rui, Yukui
Abstract: Lithium (Li) is gaining attention due to rapid rise in modern industries but their ultimate fingerprints on plants are not well established. Herein, we executed a meta-analysis of the existing recent literature investigating the impact of Li sources and levels on plant species under different growth conditions to understand the existing state of knowledge. Toxic effects of Li exposure in plants varies as a function of medium and interestingly, more negative responses are reported in hydroponic media as compared to soil and foliar application. Additionally, toxic effects of Li vary with Li source materials and LiCl more negatively affected plant development parameters such as plant germination (n = 48) and root biomass (n = 57) and recorded highly uptake in plants (n = 78), while LiNO3 has more negative effects on shoot biomass. The Li at <50 mg L −1 concentrations significantly influenced the plant physiological indicators including plant germination and root biomass, while 50–500 mg L −1 Li concentration influence the biochemical parameters. The dose-response relationship (EC50 ) ranges regarding the exposure medium of Li sources in plant species were observed 24.6–196.7 ppm respectively. The uptake potential of Li is dose-dependent and their translocation/bioaccumulation remains unknown. Future work should include full life cycle studies of the crops to elucidate the bioaccumulation of Li in edible tissues and to investigate possible trophic transfer of Li. Graphical abstract: Accumulation of Li is increasing in ecosystem and its compartments by various sources, and this might be vulnerable to plants. Image 1 Highlights: Global meta-analysis from last years articles were preformed. We observed lower levels of Li increased the plant growth and biomass but mechanism remain unknown. Higher Li levels negatively effect the physiological and biochemicals indicators of plants. EC50 values varied with exposure medium and plant species.